Linguistic Representation of The Concept of Person in The Russian Sub-Dialects of Yakutian Old-Timers - Egorovna Zhondorova, Galina (Opción, 2019)
This article studies some aspects of the linguistic worldview of the Yakutian old-timers and reveals the concept of person. Since the early 17th century, the Russian old-timers have been allegedly living among foreign languages in the Arctic territory of the Republic of Sakha (Yakutia) which is the largest subject of the Russian Federation. Old-timers are the oldest group of the Russian population living in Siberia. The study is based on the folklo- re and dialectal materials collected from representatives of this ethnic group and reflected in the "Dictionary of the Russian sub-dialects of the Yakutian old-timers". The authors of the article focus on the structure of the person concept, description of its main characteristics and identification of specific linguistic representation in the Russian sub-dialects used by old-timers. The semantics of this concept is closely connected with the peculiar lifestyle of the Yakutian old-timers.